Intraoperative Topical Antibiotics for Infection Prophylaxis in Pelvic and Acetabular Surgery. Issue 11 (November 2017) - Owen, Matthew T.; Keener, Emily M.; Hyde, Zane B.; Crabtree, Reaves M.; Hudson, Parke W.; Griffin, Russell L.; Lowe, Jason A.
Abstract : Objectives: To determine if topical vancomycin and tobramycin powder reduces the incidence of surgical site infection after pelvic ring and acetabulum fracture surgery. Design: Retrospective cohort study. Setting: University of Alabama at Birmingham, Academic Level I Trauma Center. Patients/Participants: Two hundred nineteen patients (140 meeting inclusion criteria) with pelvic and acetabular fractures who underwent open reduction and internal fixation from March 2012 to November 2013. Intervention: One gram vancomycin and 1.2 g tobramycin powder applied deep in the surgical wound of the treatment group. Main Outcome Measurements: Postoperative infection rate. Results: One hundred forty patients were included. Control group (n = 69) and treatment group (n = 71) were similar for sex, age, ethnicity, and body mass index. There was no difference between groups with regards to renal function postoperative day 2 ( P = 0.24). The risk of infection was 14.5% and 4.2% ( P = 0.04) for the control and treatment groups, respectively. No significant effect of antibiotic treatment was observed overall after adjusting for EBL (odds ratio 0.20, 95% confidence interval, 0.02–1.06). Of note, a nonsignificant 71% increase was observed among those with ≥1 L EBL (odds ratio 1.71, 95% confidence interval, 0.02–147.02). Conclusions: Topical antibiotics possibly reduce the incidence of surgical site infection after open pelvic and acetabulum fixation without increasing risk of renal impairment. The protective effect of topical antibiotics may be limited to patients with minimal intraoperative blood loss. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.